Advancing High‐Performance Mixed Matrix Membrane via Magnetically Aligned Polycrystalline Co0.5Ni0.5FeCrO4 Magnetic Spinel Nanoparticles for Effective H2/CO2 and O2/N2 Gas Separation. Issue 35 (7th November 2022) - Ashtiani, Saeed; Azadmanjiri, Jalal; Hong, Nguyen Vu; Floreková, Jana; Regmi, Chhbilal; Sofer, Zdeněk; Khoshnamvand, Mehdi; Friess, Karel
Abstract: Gas separation matrix membranes (MMMs) benefit from a combination of a polymer matrix and heterogeneous solid or liquid (nano) additives. However, improvements in mechanical strength of membrane permeability or gas selectivity are often overbalanced by morphological deficiencies, such as aggregation or sedimentation of the nanofiller, due to poor control at the nano level. Here, the controlled orthogonal magnetic field deposition of self‐invented spinel Co0.5 Ni0.5 FeCrO4 magnetic nanoparticles (SMNPs) into the cellulose triacetate (CTA) results in well‐defined gas transport pathways in the membrane and enhances gas separation performances by expanding the effective‐selective surface area. Contrariwise, the structural observation of the fabricated MMMs in the absence of the magnetic field shows precipitation and aggregation of the particles at the bottom of the membrane. The permeability and selectivity of the H2 /CO2 and O2 /N2 gas pairs surpass the 2008 and 2015 Robeson upper bounds for the controlled embedding of the SMNPs series (up to 15 wt.%) while the neat CTA or MMM with a random non‐controlled SMNPs distribution exhibits substantially lower permeability and selectivity values. This work contributes to the development of magnetic field casting as a facile technique that advances the gas transport properties of MMMs, efficient for air separation. Abstract : For the first time, self‐invented spinel Co0.5 Ni0.5 FeCrO4 magnetic nanoparticles (SMNPs) are embedded into the cellulose triacetate polymer matrix by using controlled orthogonal magnetic field deposition. The membrane morphology, filler dispersion, and overall gas transport properties are improved significantly using the new SMNPs and the incorporation method. Therefore, this work empowers new horizons for advancing MMM.